PENGARUH CONTENT MARKETING, ELECTRONIC WORD OF MOUTH (E-WOM), DAN PRICE DISCOUNT APLIKASI SHOPEE TERHADAP IMPULSE BUYING PRODUK FASHION JINISO PADA GENERASI Z DI KOTA SURABAYA - Sari, Vina Ilhamna; Rafida, Veni (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
The development of information technology encourages progress in various innovations. One form of this innovation is the creation of e-commerce. JINISO is a business actor operating in the fashion sector using Shopee e-commerce as a promotional and sales medium. The aim of this research is to analyze the influence of content marketing, electronic word of mouth and price discounts on impulse buying of JINISO fashion products among generation Z in the city of Surabaya. Respondents in this study were generation Z from Surabaya City, born in 1997 - 2012, who had impulse bought JINISO fashion products at Shopee. The sampling technique uses purposive sampling with the data collection technique using a questionnaire distributed online using Google Form. The data analysis method uses the PLSSEM method using SmartPLS 4 software. The results of this research show that content marketing, electronic word of mouth, and price discounts have a positive effect on impulse buying of fashion products in generation Z in the city of Surabaya, both partially and simultaneously. Keywords: Content marketing, Electronic word of mouth, Price discounts, Impulsive Buying